The evolution of PFAS epidemiology: new scientific developments call into question alleged “probable links” between PFOA and kidney cancer and thyroid disease - Catie Boston; Stella Keck; Avery Naperala; Justin Collins (Frontiers in Public Health)
The growing body of litigation alleging bodily injury from per- and polyfluoroalkyl substances (PFAS) exposure has put a spotlight on the available scientific literature regarding potential human health impacts, and the various data gaps within the literature. This review assesses the evolution of epidemiological findings for perfluorooctanoic acid (PFOA), a PFAS compound. In 2012, the C8 Science Panel published a series of reports determining “probable links” for certain health outcomes (including kidney cancer and thyroid disease); it was the first major research effort investigating potential adverse health effects following exposure to PFOA. At that time, there were only a handful of available studies investigating human effects (i.e., epidemiological studies). Now, over a decade later, the epidemiological body of literature for PFOA has grown substantially. As is the nature of evolving science, the additional research has spotlighted important improvements in exposure classification, confounding control, and statistical methods that strengthen more recent scientific investigations. As the body of epidemiological literature for PFAS health effects grows and evolves with improved methodology, the original C8 Science Panel’s conclusions have not been supported by more recent investigations. Within the context of general causation, while gaps remain in the body of research, more recent epidemiological findings support that there is no causal relationship between PFOA exposure and kidney cancer or thyroid disease.